2020
DOI: 10.1021/acs.energyfuels.0c02626
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Molecular Structure and Elemental Mercury Adsorption Mechanism of Biomass Char

Abstract: Based on a comprehensive study of the pyrolysis characteristics, pore structure, surface chemical functional groups, organic carbon framework structure, microcrystalline morphology, and lattice characteristics of walnut shell biochar for mercury adsorption, the structural characteristics of biochar were analyzed, and a model of the monomeric molecular structure of biochar was constructed. In addition, the density functional theory of quantum mechanics was introduced into the gas−solid adsorption reaction of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…High temperature facilitates the increase of the specific surface area of biochar, and the SSA usually enjoys an exponential increase when the pyrolysis temperature increased to a high temperature (≥500 °C) [ 38 , 39 , 40 ]. This phenomenon can be explained by the fact that chemicals, such as ethylene and esters, gradually dissipate from biomass’s outer surface as the temperature of the heating process rises (usually from 300 to 800 °C), favoring the formation of pore structure and the SSA of biochar [ 38 , 39 , 40 ]. In the same situation as above, such an exponential increase tends to result in a significant variation for the SSA of biochar between durations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High temperature facilitates the increase of the specific surface area of biochar, and the SSA usually enjoys an exponential increase when the pyrolysis temperature increased to a high temperature (≥500 °C) [ 38 , 39 , 40 ]. This phenomenon can be explained by the fact that chemicals, such as ethylene and esters, gradually dissipate from biomass’s outer surface as the temperature of the heating process rises (usually from 300 to 800 °C), favoring the formation of pore structure and the SSA of biochar [ 38 , 39 , 40 ]. In the same situation as above, such an exponential increase tends to result in a significant variation for the SSA of biochar between durations.…”
Section: Discussionmentioning
confidence: 99%
“…In the same situation as above, such an exponential increase tends to result in a significant variation for the SSA of biochar between durations. However, it is worth noting that the SSA of B-biochar and L-biochar fluctuated with time as the temperature hit 750 °C, and even an obvious decrease can be found ( Figure 1 g,h).The possible reason for this is high temperature may also induce deformation and collapse of some fine-pore structure, increasing the pore size [ 38 , 39 , 40 ]. These broken pores are likely to be overcovered by by-products of previous physiochemical reactions, such as incompletely volatilized bio-oil or oxides created by further decomposing carbonates produced following decarboxylation, ultimately lowering the specific surface area [ 23 , 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported small-scale biochar representations employing DFT calculations. ,, Ponnuchamy discussed multiscale modeling methods, such as DFT, giving details about the quantum mechanic’s basis sets, the intermolecular potentials, and the force fields employed. These small structures are used to get fundamental reactions, as the examples in Section .…”
Section: Biochar Model Generation and Advanced Atomistic Representationmentioning
confidence: 99%
“…Significant progress has been made in developing atomistic coal/kerogens models; however, it remains unclear how these methodologies can capture the structural diversity and behavior relevant to poorly organized carbonaceous materials obtained at low temperatures (less than 500 °C). This uncertainty and scale challenge arises because the current representation of biochar primarily relies on small systems consisting of only a few hundred atoms, , failing to represent biochar’s structural integrity and diversity adequately. Therefore, this paper aims to explore the potential areas for improvement in terms of atomistic representation and formation mechanisms of biochar.…”
Section: Introductionmentioning
confidence: 99%
“…As for noncarbon adsorbents, fly ash , and natural minerals display low intrinsic Hg 0 affinity due to their low surface areas and pore volumes. Although some zeolites have large surface areas, they still exhibit low inherent Hg 0 affinity owing to inadequate active sites. Metal oxides possess good Hg 0 oxidation ability; however, they are very sensitive to flue gas. Carbonaceous materials have also been widely studied owing to their ample sources and luxuriant pore structures, such as activated carbon, petroleum coke, and biochar. In addition, some novel adsorbents emerged recently, i.e., metal–organic frameworks (MOFs) and MXene (metal nitride or metal carbide) . However, their intrinsic Hg 0 affinities for pristine MOFs and MXene are very low.…”
Section: Introductionmentioning
confidence: 99%